THEORETICAL AND METHODOLOGICAL FUNDAMENTALS OF THE BRAND REVITALIZATION PROCESS - OTENKO, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In terms of rapid globalization and its impact on economic processes, increased competition in the market becomes inevitable, which directly affects the life cycle of goods and services. In addition, changing the channels of marketing communications do not always contribute to the sustainable development of brands and maintaining a stable position in the market. Under certain conditions, a brand can quickly lose relevance for consumers, forcing companies to constantly monitor the level of brand loyalty. In case of loss of positions for brand resuscitation, a number of measures are taken, and one of the most effective is revitalization. The purpose of the article is to study the theoretical and methodological foundations of the process of brand revitalization. The process of brand implementation and management has recently become new due to the constant change in economic processes. The main task of enterprises is to increase competitiveness and gain new market positions, and effective branding remains the main tool. It is noted that currently the life cycle of the brand is significantly shortened, and the main task of the company is to keep the brand in maturity for as long as possible. In case the brand is in a recession, the company should start the rebranding process, one of the options of which may be the revitalization process. Symptoms of brand aging, which can be a signal for revitalization, are outlined. A number of issues have been identified that can serve to define and develop further brand revitalization strategy. The main methods that provide brand revitalization are represented. The advantages of brand revitalization in comparison with creating a new brand are given. The implementation of the brand revitalization process has certain advantages in choosing a rebranding strategy for the company. The brand management process should take into account all threats and predict further development in accordance with the brand life cycle and determine the presence of symptoms of aging in a timely manner. If they occur, comprehensive measures should be taken, based on comprehensive changes that can breathe new life into the brand and restore its competitiveness in the market.